Development, Diagnosis and Modern Clinical Diagnostic Methods of Adenoiditis in Young Children - Olimjon oʻgʻli, Anqasov Ibratjon; JA, Khatamov (Journal of Science in Medicine and Life, 2025)
Adenoid tumors or adenoids are overgrown growths of tissue that form the base of the tonsils. The pathology develops due to inflammation of the nasopharyngeal sinuses and is more common in children. The disease occurs due to a violation of the immune system. We will tell you why the disease occurs, how its symptoms manifest themselves and how to treat adenoids. According to statistics, adenoid growths occur in every second child. Most often, the disease manifests itself at the age of 3-7, but the inflammatory process can occur later. The disease can also manifest itself in an adult. This indicates serious problems with the immune system, and doctors often resort to surgical intervention.